Integrasi Ilmu Agama dan Ilmu Umum Model Universitas Islam Negeri (UIN) Malang: Integration of Religious and General Sciences: The Universitas Islam Negeri (UIN) Malang Model - Muniron Muniron (Fenomena, 2009)
The strict dichotomy between religious and general sciences has triggered an epistemological crisis and dehumanization in Islamic education. This article examines the integration model of religious and general sciences developed by the State Islamic University (UIN) Malang using the tree of knowledge as its main metaphor. This study aims to reveal the theological and philosophical foundations of the integration model. The research employed a qualitative case study approach, combining library research and field research through interviews and documentary studies. The findings show that the integration of sciences at UIN Malang is based on theological foundations including the universality of Islamic doctrine, the concept of caliphate, the mission of rahmatan lil ‘alamin, and the principle of tawhid, as well as philosophical foundations covering ontology, epistemology, and axiology within the framework of Islamic philosophy of science. In conclusion, the tree of knowledge metaphorically describes roots as instrumental sciences, trunk as Islamic sciences, branches as modern disciplines, and fruits as faith, righteous deeds, and noble character. It is recommended that this model be adapted by other Islamic higher education institutions to end the scientific dichotomy. Dikotomi ketat antara ilmu agama dan ilmu umum telah memicu krisis epistemologis dan dehumanisasi dalam pendidikan Islam. Artikel ini mengkaji model integrasi ilmu agama dan ilmu umum yang dikembangkan oleh Universitas Islam Negeri (UIN) Malang dengan menggunakan pohon ilmu sebagai metafora utama. Penelitian ini bertujuan untuk mengungkap landasan teologis dan filosofis dari model integrasi tersebut. Penelitian menggunakan pendekatan kualitatif model studi kasus, menggabungkan penelitian kepustakaan dan penelitian lapangan melalui wawancara serta studi dokumenter. Hasil penelitian menunjukkan bahwa integrasi ilmu di UIN Malang didasarkan pada landasan teologis berupa universalitas doktrin Islam, konsep khalifah, misi rahmatan lil ‘alamin, dan prinsip tauhid, serta landasan filosofis yang mencakup ontologi, epistemologi, dan aksiologi dalam kerangka filsafat ilmu Islam. Kesimpulannya, model pohon ilmu secara metaforis menggambarkan akar sebagai ilmu alat, batang sebagai keilmuan Islam, dahan sebagai disiplin modern, dan buah sebagai iman, amal saleh, serta akhlak karimah. Rekomendasinya, model ini dapat diadaptasi oleh perguruan tinggi Islam lain untuk mengakhiri dikotomi keilmuan.